PENINGKATKAN KREATIVITAS DAN EFEKTIVITAS BELAJARMELALUI APLIKASI CANVA DALAM KURIKULUM MERDEKA - Mustofa, Hidayatul; Eko Haryono; Sariman, Sariman; Ni'matus Sa'adah, Ulfa (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
This study aims to analyze the implementation of Canva application in free curriculum-based learning to enhance creativity and learning effectiveness. The research method employed is qualitative, and the research type is descriptive-qualitative, with data collection methods including direct observation and a review of relevant literature. The findings of this study highlight the significant role of educational media in supporting the educational process. Currently, educational media places a growing emphasis on the utilization of technology and communication within the educational context. Educational media not only imparts knowledge but also stimulates the creativity and skills of learners during the learning process at school. Canva is one of the tools that can be used in the educational context. Canva is an online platform that provides various templates and features to assist educators and learners in facilitating technology-based, skill-oriented, creative, and other beneficial forms of learning.